2004
DOI: 10.1007/s00280-004-0846-6
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid enhances the susceptibility of human colorectal cancer cells to 5-fluorouracil

Abstract: Our results indicate that DHA strongly increases the antineoplastic effects of low concentrations of 5-FU. Overall, the results suggest that combinations of low doses of the two compounds could represent a chemotherapeutic approach with low toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 41 publications
5
70
1
Order By: Relevance
“…Additional researches are also needed to investigate potential effects of anti-tumor drugs administrated during chemotherapy on the erythrocyte composition of DHA. 55 FIGURE 1 -Summary of odds ratios (ORs) for breast cancer and partial Spearman's correlation coefficients between dietary intakes of fish and n-3 HUFAs and their biomarkers in erythrocyte membranes. Total seafood was defined as the sum of fish and other seafood [other fish (e.g., bone-edible small fish), shellfish, canned tuna, crustacean/ mollusk (cuttlefish, squid, octopus, shrimp and crab) and fish past products].…”
Section: Discussionmentioning
confidence: 99%
“…Additional researches are also needed to investigate potential effects of anti-tumor drugs administrated during chemotherapy on the erythrocyte composition of DHA. 55 FIGURE 1 -Summary of odds ratios (ORs) for breast cancer and partial Spearman's correlation coefficients between dietary intakes of fish and n-3 HUFAs and their biomarkers in erythrocyte membranes. Total seafood was defined as the sum of fish and other seafood [other fish (e.g., bone-edible small fish), shellfish, canned tuna, crustacean/ mollusk (cuttlefish, squid, octopus, shrimp and crab) and fish past products].…”
Section: Discussionmentioning
confidence: 99%
“…PUFA act with synergy to anticancer drugs in cells culture or in tumor-bearing animals, decreasing tumor size, reducing side effects and prolonging survival [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…DHA inhibited the growth of p53-wildtype colon cell lines (LS-174 and Colo 320 HSR) as well as of those with different p53 mutations (HT-29 and Colo 205); thus its action does not seem to be dependent on p53 status 94 . However, another study showed that DHA in vitro effects may be p53-dependent in cell lines expressing wildtype p53.…”
Section: Effects Of Dha On Cell Cycle Regulatory Proteinsmentioning
confidence: 99%
“…On the other hand, patients with amplified cMyc gene and wild type p53 have a greater response to anticancer treatment 105 . DHA was shown to increase the level of cMyc, which was related to apoptosis induction in colon cancer cells 94 . Important information was obtained from DNA microarrays which indicated reprogramming of a large number of genes and transcription factors after n-3 PUFA treatment, e.g.…”
Section: Regulation Of Specific Transcription Factors and Dha Effectsmentioning
confidence: 99%